Three generations later; Examining transnationalism, cultural preservation, and transgenerational trauma in United States Indo population - Stern, Jamie D. (Wacana, Journal of the Humanities of Indonesia, 2022)
This paper examines the relationship between transnationalism, cultural preservation, and transgenerational trauma in the United States (US) Indo population. The information being analysed was compiled by the author from two separate surveys which took place between 2012 and 2021. This data was initially intended to act as a census for the scattered US Indo community however the salient information necessitated that the census be ongoing and that another survey be developed to measure effects of lingering trauma which has been passed down generationally. The two surveys invited Indos from around the globe to participate in data collection, which led to the development of the first Indo population maps of the twenty-first century and hidden impacts of transgenerational trauma. The trauma of the Indo experience during and after World War II affected the first, second, and third generations both similarly and differently with expressions being exacerbated as the population dispersed globally.